Chemiluminometric- CFIA for the Determination of Cobalt (ll) Ion in Commercial Cobalt-Molybdenum Catalyst (K F124-3E) Used in Desulphurization Processes of Petroleum Products via Multi Gel Beads Reactor. - M.A. Shakir, Issam; F. Hassan, Zaineb (Iraqi Journal of Science, 2023)
Co(II) ion was determined by a new, accurate, sensitive and rapid method via acontinuous flow injection analysis (CFIA) with a chemiluminescence reaction based onthe oxidation of Luminol which is loaded on poly acrylic acid gel beads by hydrogenperoxide in presence of Cobalt (II) ion as a chemiluminescence catalyst. Chemical andphysical parameters were investigated to obtain the best conditions. Linear dynamicrange of Cobalt (II) ion was from 0.1-20.0 μg.ml-1 with a correlation coefficient r =0.9758, limit of detection (L.O.D) 0.2 ng/sample from the step wise dilution of lowestconcentration in the calibration graph with the percentage relative standard deviation for3 μg.ml-1 Co(ll) solution is 0.8537% (n=5). The method was applied successfully for thedetermination of Co (II) ion in CoMo catalyst type ( K F124- 3E).